2011
DOI: 10.1136/jclinpath-2011-200429
|View full text |Cite
|
Sign up to set email alerts
|

Expression of p53, p21 and cyclin D1 in penile cancer: p53 predicts poor prognosis

Abstract: In patients with PC, the expression of p53 in the primary tumour specimen can be reproducibly assessed and is negatively associated with cancer specific survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(34 citation statements)
references
References 35 publications
2
29
3
Order By: Relevance
“…The number of dysplastic cases examined was not sufficient to draw definitive conclusions in this regard. This result is similar to that obtained by Gunia et al (2011), who also reported that, from a therapeutic viewpoint, prospective clinical studies should investigate the potential benefit of Her2-targeted therapies in CIS, particularly in cases unresponsive to conventional therapeutic regimens.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The number of dysplastic cases examined was not sufficient to draw definitive conclusions in this regard. This result is similar to that obtained by Gunia et al (2011), who also reported that, from a therapeutic viewpoint, prospective clinical studies should investigate the potential benefit of Her2-targeted therapies in CIS, particularly in cases unresponsive to conventional therapeutic regimens.…”
Section: Discussionsupporting
confidence: 92%
“…However, its role in dysplasia and CIS has not been clarified (Latif et al, 2004;Hansel et al, 2008;Kolla et al, 2008;Laé et al, 2009). Gunia et al (2011) studied the so-far neglected diagnostic significance of Her2/neu protein expression profiles in flat lesions of the urinary bladder mucosa in terms of differentiating CIS from dysplasia. Moreover, Gunia et al (2011) reported heterogeneous Her2/neu expression within the mucosa under the non-CIS (dysplasia) condition.…”
Section: Introductionmentioning
confidence: 99%
“…Our recently described cohort encompasses 92 consecutive patients surgically treated for PSC between January 1993 and December 2010 in six different German hospitals 6. All patients were clinically staged to be without metastasis (cM0) before surgery using CT, MRI or chest x-ray.…”
Section: Methodsmentioning
confidence: 99%
“…dynamic sentinel node biopsy or ultrasound-guided fine needle aspiration) suffer from false-negative rates, and none of the recently reported prognostic biomarkers has been implemented on a regular basis in clinical practice yet [10,17,18,19,20,21,22,23]. …”
Section: Discussionmentioning
confidence: 99%